Livestock health and socio-economic impacts of a veterinary intervention in Maasailand: Infection-and-treatment vaccine against East Coast fever - Homewood, K.; Trench, P.; Randall, S.; Lynen, Godelieve; Bishop, B.P. (Elsevier, 2006)
In arid and semi-arid rangelands of sub-Saharan Africa, livestock are a central component of rural livelihoods and national economies, but their production is constrained by drought and disease, and exacerbated by institutional barriers and land use restrictions among other factors. Veterinary interventions may make a major difference to production measures but as with any intervention, they can also entail complex ecological and economic implications. This paper analyses the impacts of a vaccination programme for East Coast fever (ECF). ECF is the major cause of death among calves of Maasai pastoralists and agro-pastoralists and a major constraint on the livelihoods of these people. In our study sites, overall annual mortality in the calf crop due to ECF ranges from 30% to 60% depending on the rainfall (the better the rains, the higher the ECF mortalities). Our study explores the implications of vaccination for pastoralist livestock production, development and poverty and considers the potential impacts on rangeland and wildlife. Livestock mortality, sale, slaughter and exchange were measured using a multi-round survey of 72 households and a register of 1528 cattle in two study areas of different ecology and epidemiology. Livestock performance differed between the two areas, with the highland area showing higher background levels of mortality of unvaccinated animals. The infection-and-treatment method of vaccination has a major and highly significant impact on survival in both areas. Uptake of vaccination is strongly associated with a measure of wealth that includes livestock numbers and economic security, and medium and poor pastoralist households find it hard or impossible to access the full benefits of the vaccine. In one study site, vaccination was more frequent for male animals than females, suggesting an investment in vaccination for improved terms of trade. Vaccination could therefore improve livestock production without driving increasing herd numbers. However, the degree to which increasing survival due to vaccination is offset by increasing volume of trade requires further monitoring as those calves vaccinated at the start of the project reach economic maturity. Our study shows no link between vaccine uptake (or volume of trade) and scale of cultivation, suggesting little cross-investment between these livelihood activities. Vaccination potentially holds positive implications for rangeland and wildlife ecology. However, the logistics and economics of access to the vaccine mean that, under the current system of distribution, it could be driving socio-economic differentiation, rather than alleviating poverty. Alternative systems are suggested. Government and donor promotion of this and comparable interventions need to consider the poverty impacts and take measures to widen access.